Pathways to inclusive and equitable quality early childhood education for achieving SDG4 goal—a scoping review - Rad, Dana; Redeş, Adela; Roman, Alina; Ignat, Sonia; Lile, Raul; Demeter, Edgar; Egerău, Anca; Dughi, Tiberiu; Balaş, Evelina; Maier, Roxana; Kiss, Csaba; Torkos, Henrietta; et al. (Frontiers in Psychology, 2022)
According to Sustainable Development Goal 4.2 (SDG 4.2), Equal Access to Quality Pre-Primary Education, governments throughout the world are working to ensure that all children have access to high-quality early childhood development, care, and pre-primary education by 2030. In order to organize available evidence into a coherent framework, the current scoping review represents an exploratory synthesis addressing the broad question of what qualitative and inclusive Early Childhood Education and Care strategies are currently being established globally to achieve SDG4 targets. The goal of this scoping review in this respect, was to map the available research and offer an overview of micro-, meso-, and macro-level perspectives on evidence-based interventions and strategies, for the promotion of SDG4 globally. A layered model of early childhood education that is both inclusive and egalitarian education emerged. Conclusions and implications are discussed and research directions are presented for further documenting systematic reviews based on the current layered model. Policy argumentation is suggested for the institutional inclusive and equitable quality early childhood education assessment.